2021
DOI: 10.1007/s00417-021-05236-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thrombospondin-1 in conjunctival squamous cell carcinoma is correlated to the Ki67 index and associated with progression-free survival

Abstract: In this study, there were significant differences in 45 genes between conjunctival carcinoma in situ (Tis) and advanced squamous cell carcinoma (SCC).Thrombospondin-1 had the highest frequency of different expression.・ Thrombospondin 1 showed significantly different expression between Tis and advanced SCC (≤T1). There was a significant correlation between thrombospondin-1 expression and the Ki67 index associated with tumor progression.・ Thrombospondin-1 expression correlated with progression-free survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…There was a significant difference between the Tis and Tadv groups. Increased expression of CXCR4 in the Tadv group was also confirmed by both immunohistochemical analysis and our previous analysis of mRNA expression [ 24 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There was a significant difference between the Tis and Tadv groups. Increased expression of CXCR4 in the Tadv group was also confirmed by both immunohistochemical analysis and our previous analysis of mRNA expression [ 24 ].…”
Section: Discussionsupporting
confidence: 75%
“…Expression of mRNA for CXCR4 , HIF-1α , IL-6 , NFKB1 , and ROCK1 differed significantly ( P <0.05) between the Tis and Tadv groups. We have already published some of these results [ 24 ]. the multiple correction test was also performed by the Benjamini-Yekutieli method, however in that case were no significant difference (P <0.05).…”
Section: Resultsmentioning
confidence: 99%
“… 17 In an East Asian cohort of 31 patients, transcriptomic comparison between carcinoma in situ and advanced disease revealed significant differences in the expression of 45 genes, with thrombospondin-1 ( THBS1 ) being the most biologically important. 18 In a study of 41 Ugandan patients, TP53 codon 72 polymorphisms were found to be an independent risk factor for high-grade conjunctival intraepithelial neoplasia and invasive conjSCC, regardless of HIV status. 19 In a report from Saudi Arabia, TP53 overexpression was found in 14 of 23 (61%) conjSCCs and correlated with poor clinical outcome.…”
mentioning
confidence: 99%